1983
DOI: 10.1111/j.1751-1097.1983.tb04530.x
|View full text |Cite
|
Sign up to set email alerts
|

RECOVERY OF Escherichia coli K‐12 FROM NEAR‐ULTRAVIOLET RADIATION‐INDUCED MEMBRANE DAMAGE

Abstract: A wild‐type Escherichia coli K‐12 strain was irradiated with broad‐band near‐ultraviolet radiation (from Black‐Light Blue fluorescent lamps) and after holding at 37°C for various times in a complex recovery medium, was assessed for viability on either complex medium (YENB) or minimal medium containing a high inorganic salt content. A near‐ultraviolet radiation fluence was used which reduced the surviving fraction to approximately 10% when assessing for viability on the complex medium plates. A near‐ultraviolet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Cytochromes are part of the membrane-bound electron transport chain and may thus serve to target NUV damage to membranes (43). Membrane damage has been reported to be involved in NUV toxicity (20,21,28). We have also observed that cells became sensitive to killing by high salt levels after NUV treatment, which is consistent with this involvement of membrane damage in NUV toxicity.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Cytochromes are part of the membrane-bound electron transport chain and may thus serve to target NUV damage to membranes (43). Membrane damage has been reported to be involved in NUV toxicity (20,21,28). We have also observed that cells became sensitive to killing by high salt levels after NUV treatment, which is consistent with this involvement of membrane damage in NUV toxicity.…”
Section: Discussionsupporting
confidence: 77%
“…Membrane damage has been reported to be involved in the toxic effects of NUV (20,21,28). This conclusion was based on the observation that cells are sensitive to high salt levels after NUV exposure (20,28) and on the influence of membrane composition on killing by NUV (21). We attempted to reproduce these results in our system by NaCl treatment of cells after NUV exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Moss and Smith (1981) demonstrated oxygen dependent salt sensitivity of Escherichiu coli K-12 to near UV radiation, and suggested membrane damage as a major contributor to cell inactivation. In support of this Kelland et al (1983a) showed that bacitracin, an antibiotic which inhibits membrane synthesis, could decrease recovery of the same strain of E. coli from near UV induced salt sensitivity. An action spectrum for UV radiationinduced membrane damage in E. coli K-12 obtained (Kelland et al, 1983b).…”
Section: Introductionmentioning
confidence: 74%
“…Inhibition Error bars represent standard deviations of processes at the membrane level can explain the observed reductions in monomer incorporation rates upon UV exposure. However, the slight stimulation in glucose incorporation rates during the irradiation period suggests that membrane impairment is not accompanied by cell death (Kelland et al 1983;Jeffrey et al 1996).…”
Section: Effects Of Uv-b On Bacterial Heterotrophic Metabolismmentioning
confidence: 99%